Differential diagnostic value of tumor markers and contrast-enhanced computed tomography in gastric hepatoid adenocarcinoma and gastric adenocarcinoma - Dong, Congsong; Wang, Yanling; Gu, Xiaoyu; Lv, Xiaojing; Ren, Shuai; Wang, Zhongqiu; Dai, Zhenyu (Frontiers in Oncology, 2023)
Objective: To investigate the effectiveness of tumor markers and contrast-enhanced computed tomography (CE-CT) in differentiating gastric hepatoid adenocarcinoma (GHA) from gastric adenocarcinoma (GA). Methods: A retrospective study consisting of 160 patients (44 GHA patients vs 116 GA patients) who underwent preoperative CE-CT was performed. Preoperative serum concentrations of the tumor biomarkers and CT imaging features were analyzed, including AFP (alpha-fetoprotein), CEA (carcinoembryonic antigen), CA19-9 (carbohydrate antigen 19-9), CA125 (carbohydrate antigen 125), tumor location, growth pattern, size, enhancement pattern, cystic changes, and mass contrast enhancement. Multivariate logistic regression analyses were adopted to evaluate useful tumor markers and CT imaging features in differentiating GHA from GA. Results: When compared to GA, GHA showed higher serum AFP [13.27 ng/ml (5.2~340.1) vs. 2.7 ng/ml (2.2~3.98), P < 0.001] and CEA levels [4.07 ng/ml (2.73~12.53) vs. 2.42 ng/ml (1.38~4.31), P < 0.001]. CT imaging showed GHA with higher frequencies of tumor location at gastric antrum (P < 0.001). GHA had significantly lower attenuation values at the portal venous phase [PCA, (82.34 HU ± 8.46 vs 91.02 HU ± 10.62, P < 0.001)] and delayed phase [DCA, (72.89 HU ± 8.83 vs 78.27 HU ± 9.51, P < 0.001)] when compared with GA. Multivariate logistic regression analyses revealed that tumor location, PCA, and serum AFP were independent predictors in differentiating between GHA and GA. The combination of these 3 predictors performed well in discriminating GHA from GA with an AUC of 0.903, sensitivity of 86.36%, and specificity of 81.90%. Conclusions: Integrated evaluation with tumor markers and CT features, including tumor location, PCA, and serum AFP, allowed more accurate differentiation of GHA from GA.